Hydrodynamic loads on a circular cylinder surrounded by two, four and eight wake-control cylinders. (1st April 2018) - Silva-Ortega, M.; Assi, G.R.S.
Abstract: The hydrodynamic loads of mean drag and fluctuating lift are presented for a circular cylinder fitted with 2, 4 and 8 wake-control cylinders positioned around its circumference. The device is fitted around the body to interact with the flow in the near wake and control vortex shedding. The efficiency regarding lift suppression and drag reduction has been investigated for nine different cases varying the diameter of the control cylinders and their relative gap from the wall. All cases have been compared with the hydrodynamic forces of a plain cylinder. The configuration with 4 control cylinders, gap ratio of G / D = 0.05 ( G is the gap between the control cylinders and the main cylinder of diameter D ) and diameter ratio of d / D = 0.06 ( d is the diameter of the control cylinders) produced the lowest drag when compared to all other configurations: mean drag coefficient was 0.75, approximately 50% lower than that of a bare cylinder. Experiments have been conducted in a free-surface water channel at moderated Reynolds numbers between 5000 and 50, 000. Highlights: We present hydrodynamic loads of mean drag and fluctuating lift for a circular cylinder with 2, 4 and 8 control cylinders (c-c). Cases with 4 and 8 c-c performed better. The actual position of the c-c around the main body is important. The configuration with 4 c-c with G/D = 0.05 and d/D = 0.06 produced a 50% drag reduction.